2014
DOI: 10.3389/fgene.2014.00285
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the neural transcriptome and alcohol interference during development

Abstract: Alcohol intoxicated cells broadly alter their metabolites – among them methyl and acetic acid can alter the DNA and histone epigenetic codes. Together with the promiscuous effect of alcohol on enzyme activities (including DNA methyltransferases) and the downstream effect on microRNA and transposable elements, alcohol is well placed to affect intrinsic transcriptional programs of developing cells. Considering that the developmental consequences of early alcohol exposure so profoundly affect neural systems, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 129 publications
0
28
0
1
Order By: Relevance
“…Similarly, in dentate granule neurons of the developing mouse hippocampus, a methylation gradient correlates with the outside‐in pattern of neuronal maturation (Chen et al., ). Studies of rat and mouse brains have demonstrated associations between development and histone PTM changes (Cho et al., ; Hahn et al., ; Podobinska et al., ; Resendiz et al., ; Zhang et al., ). In order for stem cells to change from totipotency to pluripotency, active histone PTMs are present on gene promoters such as H3K27ac and H3K4me3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in dentate granule neurons of the developing mouse hippocampus, a methylation gradient correlates with the outside‐in pattern of neuronal maturation (Chen et al., ). Studies of rat and mouse brains have demonstrated associations between development and histone PTM changes (Cho et al., ; Hahn et al., ; Podobinska et al., ; Resendiz et al., ; Zhang et al., ). In order for stem cells to change from totipotency to pluripotency, active histone PTMs are present on gene promoters such as H3K27ac and H3K4me3.…”
Section: Discussionmentioning
confidence: 99%
“…When a brain cell is fully differentiated, repressive histone PTMs such as H3K27me3 are typically dominant (Podobinska et al., ). H3K4me2 and histone acetylation levels increase during differentiation of mouse NPCs (Resendiz et al., ; Zhang et al., ). Compared to NPCs, mature mouse cortical neurons are enriched in histone acetylation marks (Cho et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, alterations to chromatin structure induced by environmental and/or nutritional insults have become an attractive explanation for the persistence of exposure effects into subsequent life stages (Feil & Fraga, 2011). Indeed, numerous studies have demonstrated that ethanol (EtOH) has the capacity to alter chromatin structure, suggesting that epigenetic mechanisms are relevant to the dysgenesis associated with FASDs (Basavarajappa & Subbanna, 2016; Mead & Sarkar, 2014; Resendiz, Mason, Lo & Zhou, 2014; Ungerer, Knezovich & Ramsay, 2013). For example, work from a number of laboratories have demonstrated both acute and long-term EtOH exposures influence patterns of DNA methylation (Ungerer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A key finding is that during the formation of multi-layer cytoarchitecture of the cortex, 5mC and 5hmC marks are dynamically established in the progression of neuroprogenitor cell differentiation, which is in many ways similar to our previous observation of neuroepithelial cells (NEs) in neural tube and hippocampus formation. Commonly, the escalation of 5mC in the NEs marks the preparation and initiation of specification toward neural cells, likely occurring to assist in the down-regulation of multi-potent and proliferation genes (Kim et al, 2014; Resendiz, Mason, Lo, & Zhou, 2014). 5mC subsequently declines as migration begins from the upper limits of the VZ and through the IZ and enters a second cycle of up-regulation in the upper cortical layers as maturing neurons prepare for synaptogenesis.…”
Section: Discussionmentioning
confidence: 99%